2003
DOI: 10.1128/jb.185.12.3596-3605.2003
|View full text |Cite|
|
Sign up to set email alerts
|

Escherichia coli O157:H7 Shiga Toxin-Encoding Bacteriophages: Integrations, Excisions, Truncations, and Evolutionary Implications

Abstract: As it descended from Escherichia coli O55:H7, Shiga toxin (Stx)-producing E. coli (STEC) O157:H7 is believed to have acquired, in sequence, a bacteriophage encoding Stx2 and another encoding Stx1. Between these events, sorbitol-fermenting E. coli O157:H ؊ presumably diverged from this clade. We employed PCR and sequence analyses to investigate sites of bacteriophage integration into the chromosome, using evolutionarily informative STEC to trace the sequence of acquisition of elements encoding Stx. Contrary to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
186
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(201 citation statements)
references
References 56 publications
12
186
3
Order By: Relevance
“…Although the frequency of inversions cannot be estimated from optical maps of temporally and geographically dispersed strains, the five sets of inversions in EDL933 identified in the laboratory studies arose during 20, 30 and 50 subcultures (Iguchi et al, 2006). Regarding the frequency of inversions and prophage changes in chromosomes, dissimilarities in the stx1 and stx2 gene profiles of particular O157 : H7 strains have been demonstrated to be not only the result of the heterogeneity in phages containing the toxin genes but also due to the unexpected variability in their integration sites (Shaikh & Tarr, 2003). Moreover, polymorphic PCR amplification patterns were an early indicator that insertions and deletions dominated the differences between O157 : H7 strains (Kudva et al, 2002a, b); many of these polymorphisms were found within prophages.…”
Section: Discussionmentioning
confidence: 99%
“…Although the frequency of inversions cannot be estimated from optical maps of temporally and geographically dispersed strains, the five sets of inversions in EDL933 identified in the laboratory studies arose during 20, 30 and 50 subcultures (Iguchi et al, 2006). Regarding the frequency of inversions and prophage changes in chromosomes, dissimilarities in the stx1 and stx2 gene profiles of particular O157 : H7 strains have been demonstrated to be not only the result of the heterogeneity in phages containing the toxin genes but also due to the unexpected variability in their integration sites (Shaikh & Tarr, 2003). Moreover, polymorphic PCR amplification patterns were an early indicator that insertions and deletions dominated the differences between O157 : H7 strains (Kudva et al, 2002a, b); many of these polymorphisms were found within prophages.…”
Section: Discussionmentioning
confidence: 99%
“…SBI genotypes of strains were determined as published (Besser et al, 2008;Shaikh & Tarr, 2003) with minor modification. Amplification of yehV or wrbA was performed in two multiplex PCRs for detection of bacteriophage integration and amplification of stx 1 and stx 2 genes was performed in two uniplex reactions as described (Botteldoorn et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Some investigators previously suggested that tir (255T) harbouring strains are more virulent in humans than tir (255A) harbouring strains Franz et al, 2012;Mellor et al, 2013). Shiga toxin bacteriophage insertion (SBI) site analysis relies on amplification of the stx toxin genes (stx 1 and stx 2 ) and the insertion site junctions of their encoding bacteriophages that can be used as a valuable genotyping technique to distinguish E. coli O157 : H7 strains, based on their distribution, gene expression and virulence potential (Besser et al, 2008;Shaikh & Tarr, 2003). Moreover, Shiga toxin 2 variants (stx 2a and stx 2c ) and stx 2 -Q antiterminator gene variants are clinically relevant genetic markers among E. coli O157 : H7 (Ahmad & Zurek, 2006;Persson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the stx phages present in E. coli O157 : H7 strains, two insertion sites were first described as preferred: wrbA and yehV (Shaikh & Tarr, 2003;Besser et al, 2007). However, there are other integration sites described for stx phages in O157, such as sbcB, argW and yecE (De Greve et al, 2002;Mellor et al, 2012;Shringi et al, 2012).…”
Section: Insertion Site Diversitymentioning
confidence: 99%